Raman scattering in crystals with order-disorder type phase transition - Ivankiv, Ya. (Condensed Matter Physics, 1999)
The theory based on the “operator” two-time Green functions formalism applied for the construction of the polarizability operators entering the general expression for the effective cross-section of Raman scattering is developed. The presented microscopic scheme is applied to the investigation of the ferroelectrics with hydrogen bonds.